2021
DOI: 10.1007/s00344-021-10411-5
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Nitric Oxide Confers Tolerance to Cr(VI) in Maize (Zea mays L.) Seedlings by Modulating Endogenous Oxido-Nitrosative Events

Abstract: The use of exogenous compounds such as 'gasotransmitter' molecules is a well-established agronomic strategy to improve the crop tolerance to environmental stresses. In this current work, when Cr (200 µM) was combined with the nitric oxide (NO) generator sodium nitroprusside SNP, 500 µM) there was a suppression of metal-induced alterations in embryo growth. Exogenous NO produced by SNP reduced the accumulation of toxic hydrogen peroxide and methylglyoxal and stress-linked proline in Cr-treated seedlings. Chromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…In Cd‐exposed pea plants ( Pisum sativum L., cv Lincoln), Barroso et al (2006) observed that the content of GSNO in collenchyma cells showed a marked decrease ( P < 0.05). Cr treatments reduced GSNO levels for radicles of maize ( Zea mays L.) (Kharbech et al, 2022). Application of GSNO‐reduced cell death, H 2 O 2 level, oxidative damage, and elevated proline content, indicating that NO donor GSNO mitigated the toxicity of Cd in plants (Xu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In Cd‐exposed pea plants ( Pisum sativum L., cv Lincoln), Barroso et al (2006) observed that the content of GSNO in collenchyma cells showed a marked decrease ( P < 0.05). Cr treatments reduced GSNO levels for radicles of maize ( Zea mays L.) (Kharbech et al, 2022). Application of GSNO‐reduced cell death, H 2 O 2 level, oxidative damage, and elevated proline content, indicating that NO donor GSNO mitigated the toxicity of Cd in plants (Xu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…NO can increase the activity of both enzymatic and non-enzymatic antioxidants to scavenge ROS and lipid peroxidative substrates, and therefore, protect cells from oxidative damage against heavy metal stress by reducing their uptake accumulation, and translocation. Consequently, NO improves ionic homeostasis and provides tolerance to metal stress [ 16 ]. Moreover, NO is a signaling and highly reactive biomolecule that has the ability to alter the structure and activity of proteins [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, depending on the type of donor and the concentration when supplied exogenously, NO can function as a beneficial or harmful molecule in plants. S-nitrosoglutathione (GSNO) is an S-nitrosylated derivative of cellular thiol glutathione (GSH) and is considered to be one of the most important NO donors [ 16 ]. GSNO has been found to have a positive affect for long periods as a NO source against water stress in sugarcane [ 17 ].…”
Section: Introductionmentioning
confidence: 99%